HYPERO-HYPONYMIC RELATIONS IN THE VERBALIZATION OF SPATIAL AND TEMPORAL CATEGORIZATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The abstract is devoted to the study of the verbalization of space and time categories in hyper-hyponymic relations in Kyrgyz linguistics. The peculiarities of the study of the semantics of the verbalization in the temporal and spatial categories of derived and innate verbs in the semantic field are considered.
Keywords: hyperonym, hyponym, categorization, verbalization, semantic field, temporal category, spatial category